A Case Series on the Use of Diode Lasers in Soft Tissue Applications in Pediatric Dentistry - Padma Praveena Mavuri; Manikya K Nanduri; Kotra Shivani; Manchikalapati N Jyothi; Tripura P Javangula (Journal of South Asian Association of Pediatric Dentistry)
Aim and background: In pediatric dentistry, laser technology offers a viable treatment modality for treating kids and adolescents. By providing an excellent hemostatic effect, ease of application, limited use of postoperative antibiotics, and minimal discomfort to the child, lasers create a stress-free environment for both the clinician and the child. Case description: This paper describes a series of four cases treated with a diode laser. Case 1: a 6-year-old child diagnosed with ankyloglossia. Case 2: a 12-year-old child diagnosed with a mucocele. Case 3: an 8-year-old child needing exposure of unerupted incisors. Case 4: a 16-year-old with a pericoronal flap around the right mandibular third molar. A continuous-wave diode laser set at 980 nm was recommended as the line of treatment for each patient. Conclusion: The present case series recommends the use of a 980 nm diode laser in oral soft tissue procedures due to its versatility and the benefits associated with laser surgery. Clinical significance: There were no complications following surgery, and all patients reported uneventful healing. At follow-up appointments, positive results from laser surgery were noted.